PROSES BERPIKIR MATEMATS SISWA DITINJAU DARI SELF-CONFIDENCE MATERI GARIS DAN SUDUT - Ranti, Ruri; Yusmin, Edy; Halini, Halini (Jurnal AlphaEuclidEdu, 2023)
This study aims to determine and describe the mathematical thinking process of students in terms of self confidence in the material of lines and angles. The research method used is descriptive qualitative. This research involved 20 students of class VII SMP Negeri 4 Sungai Raya. The results of this study indicate that students with mathematical thinking processes with high self-confidence when solving line and angle problems are able to identify and translate information into mathematical form, students also apply the concept of lines and angles, can identify elements of the concept then develop it into a procedure, re-examine answers and plan problem solving. Students whose mathematical thinking process with moderate self-confidence when solving line and angle problems are able to identify and translate information into mathematical form, able to apply the concept of line and angle, can identify elements of the concept then developed into procedures, but students answer only until explaining and checking back and cannot plan problem solving. Students whose mathematical thinking process with low self-confidence are only able to identify and translate information into mathematical form and apply the concept of lines and angles, but cannot identify elements of the concept, cannot develop it into a procedure and also cannot explain and check back each step and cannot plan problem solving.